PREVALENSI INFEKSI CACING USUS PADA SISWA SEKOLAH DASAR DI DESA PED KABUPATEN KLUNGKUNG - Dyatmika, I Nyoman Adidana Jaya; Diarthini, Ni Luh Putu Eka; Laksemi, Dewa Ayu Agus Sri; Damayanti, Putu Ayu Asri (E-Jurnal Medika Udayana, 2023)
Background : Intestinal worms is still a health problem in Indonesia, intestinal worm infections are included in neglected disease, which means this disease has not received special attention from the sufferer. Ped Village, Klungkung Regency is an area with warm temperatures, sandy loamy soil, and clean water has not been reached. This factors raise the suspicion that in Ped Village, Klungkung Regency there is one or more species of intestinal worms, so it is very important to determine the prevalence of intestinal worm infections in elementary school students Ped Village, Klungkung Regency. Aims : To determine prevalence of intestinal worm infection in elementary school students in Ped Village, Klungkung Regency. Methods : This study uses a descriptive cross sectional method, where researchers will determine the prevalence of intestinal worm infection through fecal samples examined by the kato-katz method, intestinal worms are identified under a microscope with an objective magnification of 10x to 40x. Results : There were 139 respondents who met the inclusion criteria of the study, including 72 men and 67 women, from the results of laboratory tests, prevalence of intestinal worm infection was 0.7%. Infection occurs in male children with the worm species Enterobius vermicularis. Conclusion : The prevalence of intestinal worm infection was 0.7% in elementary school students Ped Village, the species found was Enterobius vermicularis in boys. The cause of this infection is thought due to environmental and personal hygiene factors which are still not well maintained in students. Keywords: Intestinal worm infection, prevalence, elementary school children, Ped village